2013
DOI: 10.1021/jp409874c
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Fluorescence Quenching and Enhancement of Porphyrin Sensitizers on TiO2 Films and in PMMA Films

Abstract: Three highly efficient porphyrin sensitizersYD2, YD2-oC8, and YD30, either sensitized on TiO 2 films or embedded in PMMA filmswere investigated using electrophotoluminescence (E-PL) spectra. Under both thin-film conditions, on application of an external electric field we observed the quenching of fluorescence of push−pull porphyrins (YD2 and YD2-oC8) and a slightly enhanced fluorescence of the reference porphyrin without an electron donor group (YD30). A nonfluorescent state with charge separation (CS) is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Remarkable field-induced quenching of PL of DN488 shows that nonradiative relaxation process­(es) following photoexcitation are enhanced by application of F in DN488. The relaxation process of these dyes which is affected by F may be regarded as the field-induced exciton dissociation which produces a hole and electron pair because a good correlation exists between the photon energy conversion efficiency of the photovoltaic cells constructed with these dyes and the magnitude of the field-induced quenching, as in the case of push–pull porphyrin dyes attached on TiO 2 . In other words, the dye which shows efficient field-induced exciton dissociation is regarded as a dye sensitizer suitable for DSSC.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable field-induced quenching of PL of DN488 shows that nonradiative relaxation process­(es) following photoexcitation are enhanced by application of F in DN488. The relaxation process of these dyes which is affected by F may be regarded as the field-induced exciton dissociation which produces a hole and electron pair because a good correlation exists between the photon energy conversion efficiency of the photovoltaic cells constructed with these dyes and the magnitude of the field-induced quenching, as in the case of push–pull porphyrin dyes attached on TiO 2 . In other words, the dye which shows efficient field-induced exciton dissociation is regarded as a dye sensitizer suitable for DSSC.…”
Section: Discussionmentioning
confidence: 99%
“…E-PL spectra and E-A spectra were measured by the same system and procedures as reported elsewhere [13][14][15][16][17][18][19][20][21][22]. PMMA (MW = 120,000) was obtained from Aldrich and purified by a precipitation with a mixture of benzene and methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of these spectra provide unique information about the differences in electric dipole moment (μ) and molecular polarizability (α) between the ground state and excited states. These spectra have also been used to probe field-induced molecular orientation [19,20], to examine the stability of organic light-emitting diode materials [21], and to examine the efficiency of dye-sensitized solar cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,25 ] We showed that an external electric field affects the fluorescence intensities of locally excited states of isolated donors or acceptors, and exciplexes, and thereby alters the rates of photoinduced electron transfer of methylene‐linked compounds of phenanthrene and N,N‐dimethylaniline, carbazole and methyl terephthalate, and push‐pull‐type porphyrins in a poly(methyl methacrylate) (PMMA) polymer film. [ 26–30 ] These studies of the effect of an electric field on the fluorescence of push‐pull porphyrins embedded in PMMA and sensitized on TiO 2 revealed that quenching is efficient for sensitized films on TiO 2 because of a rapid injection of electrons into TiO 2 . [ 30 ] Electric‐field effects on the fluorescence of π‐conjugated polymers such as poly[2‐(phenyl)‐3‐(4′‐(3,7‐dimethyloctyloxy)phenyl)‐1,4‐phenylenevinylene‐ co ‐2‐(11′‐decylsulfanylundecanyloxy)‐5‐methoxy‐1,4‐phenylene vinylene] (S3‐PPV) and rr‐P3HT were similarly examined.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26–30 ] These studies of the effect of an electric field on the fluorescence of push‐pull porphyrins embedded in PMMA and sensitized on TiO 2 revealed that quenching is efficient for sensitized films on TiO 2 because of a rapid injection of electrons into TiO 2 . [ 30 ] Electric‐field effects on the fluorescence of π‐conjugated polymers such as poly[2‐(phenyl)‐3‐(4′‐(3,7‐dimethyloctyloxy)phenyl)‐1,4‐phenylenevinylene‐ co ‐2‐(11′‐decylsulfanylundecanyloxy)‐5‐methoxy‐1,4‐phenylene vinylene] (S3‐PPV) and rr‐P3HT were similarly examined. [ 31–34 ] Upon application of an electric field S3‐PPV showed an enhanced or quenched PL dependent on the excitation wavelength.…”
Section: Introductionmentioning
confidence: 99%